Exploring gender disparities in burn injuries: A retrospective study at a burns centre in Karachi, Pakistan - Samia Tasleem; Muhammad Abdul Wasay Zuberi; Muhammad Sheheryar Hussain; Syed Muhammad Moaaz Bin Sultan; Ahmed Ibrahim; Hussain Haider Shah; Hasan Tariq; Arqam Bin Aijaz (Elsevier, 2023)
Introduction: Burn is defined as any injury due to heat or acute trauma, according to the International Society of Burns Injury (ISBI). A neglected aspect of our country is the gender-specific pattern of burn injuries. This study aims to highlight the gender-based disparities of burns injuries and overcome the drastic effects of burns on an individual's life. Method: The data from the burns centre of Dr Ruth.K.M.Pfau Civil Hospital Karachi from Jan 1, 2021, to Dec 31, 2021, were retrospectively analyzed to perform this study. Different variables such as aetiology, circumstances, residence, age, TBSA, degree and occupation were recorded from the patient's files. They were compared by gender to find out any existing correlation. Results: The estimated sample size was 375, 180(48%) females, and 195(52%) were burned males. A significant correlation was found for gender with a degree of burns, aetiology, age, occupation, and residence. Whereas circumstances of burns and TBSA were non-significantly correlated to gender. Conclusion: In conclusion, our study determined that men most commonly suffer from burn injuries. In contrast, thermal injury is the most dominant etiological factor in every age group in both genders. Several risk factors are associated with a specific gender, requiring adaptive prevention and management approaches to culminate this issue.